Von Willebrand factor/ADAMTS‐13 interactions at birth: implications for thrombosis in the neonatal period. (6th February 2019) - Katneni, Upendra K.; Ibla, Juan C.; Hunt, Ryan; Schiller, Tal; Kimchi‐Sarfaty, Chava
Abstract : Summary: von Willebrand factor (VWF) and its cleaving protease ADAMTS‐13 (A Disintegrin and Metalloproteinase with Thrombospondin type 1 motif, member 13) are essential components to hemostasis. These plasma proteins have also been implicated in a number of disease states, including those affecting children. The best described abnormality is the congenital form of thrombotic thrombocytopenic purpura (TTP) resulting from germline mutations in the ADAMTS‐13 gene. The VWF/ADAMTS‐13 interaction has more recently emerged as a causative risk factor in the pathogenesis of pediatric stroke and secondary microangiopathies. There is now increasing interest and need to measure these coagulation factors during the neonatal period and throughout childhood. Methods adopted from a multitude of technically diverging studies have been used to understand their role during this period. To date, studies of VWF/ADAMTS‐13 in this group of patients have reported conflicting results, which makes interpreting values in the clinical setting especially challenging. In this review we describe the historical evolution of the methodology used to measure VWF/ADAMTS‐13 and how it may influence the results obtained during the first days of life. We review the individual assays used to analyze VWF/ADAMTS‐13 as well as published reference values. Finally, we bring attention to the potential pathophysiologic role of VWF/ADAMTS‐13 in neonatal thrombosis. This has significant implications because the pathologic processes that explain thrombosis in neonates remain poorly characterized and thromboembolism remains a significant source of morbidity and mortality, particularly in sick children.